Parents' understanding of gender towards parenting to teenagers - Demaris Cristina Sailana (Indonesian Journal of Social Sciences, 2020)
Gender problems have become daily topics of discussion. The relationship between gender and parenting in a family can also cause different problems because the understanding among individuals in the family is also different. The purpose of this study was to determine the understanding of parents about gender and to identify the way parents provide parenting to boys and girls. The research method used in this study was a descriptive qualitative approach. The informants in this research were parents who have teenaged children, either boys or girls, or both of them. The results of this study indicate that parents in Claket Village did not understand the differences between gender and sex because they still distinguished the tasks based on sex. The way that the parents used to provide parenting to boys and girls was to involve their children directly in doing their parents’ activities.